Evaluation of Publication Performance in the Field of Public Administration in Indonesia: A Bibliometric Approach - Mahmud, Usamah; Muliati (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal